PTH-154 Gastrointestinal Late Effects of Cancer Care – Is There an Unmet Need in Primary Care?. (17th August 2016) - Stacey, R; Ludlow, H; Turner, J; Green, J
Abstract : Introduction: Gastrointestinal late effects of pelvic cancer treatment are common and these patients are recognised as having an unmet need within the health service at present. We have recently set up a dedicated clinic to deal with late effects of cancer care in Cardiff, however noted that all our referrals were received from secondary care oncology. We did not receive any primary care referrals. We aimed to assess the current knowledge of general practitioners in Wales and assess their referral practice. Methods: An online questionnaire comprising of 22 questions were sent via email to all GP practices in Wales. 63 GPs replied and completed the questionnaire. The results were collected anonymously using survey monkey online software. Results: 63 GPs replied (39 GP Partners, 9 Salaried GPS, 1 GP locum, 14 GP registrars) from all regions of Wales. 78.33% reported having previously seen patients with new gastrointestinal symptoms after treatment for pelvic cancer, (e.g. after radiotherapy) in their practice. The prevalence of late effects of cancer care was underestimated by 96.55% and the impact on quality of life was also underestimated by 39.65% as described in the literature. 1 Most GPs reported that although they were aware of the condition, they only saw less than 1 case per month. 25.86% of GPs felt confident with basic cases, but would need sub-specialty advise with more complex cases felt that they needed expert help for most cases. All other respondents felt either were not confident/ had no experience or somewhat confident, but have minimal experience. 84.48% wanted more education on this topic. Conclusion: GPs appear to underestimate the prevalence and impact of late effects on patients. They recognise that expertise is needed to treat these patients and that they lack both this training and frequent exposure to these patients, but also are keen for further education. The treatment of GI late effects has benefitted in secondary care within the last 5 years due to increased exposure, but this has yet to filter down into primary care. There is almost certainly an unmet need in primary care which needs to be addressed via better communication of services available in secondary care and current practice. Clinicians, NHS trusts and supportive charities should aim to improve the awareness of this under recognised condition. Reference: 1. Andreyev J. Gastrointestinal symptoms after pelvic radiotherapy: a new understanding to improve management of symptomatic patients. Lancet Oncol 2007 Oct 25;8 (11):1007–17. Disclosure of Interest: None Declared